Weed Management in Peanuts - J. A. Ferrell; G. E. MacDonald; Pratap Devkota (EDIS)
Successful weed control in peanuts involves use of good management practices in all phases of peanut production. This 11-page document lists herbicide products registered for use in Florida peanut production, their mode of actions group, application rate per acre and per season, and reentry interval. It also discusses the performance of these herbicides on several weeds under Florida conditions. Written by J. A. Ferrell, G. E. MacDonald, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised May 2020.